Lean Blockchain Systems Thinking : Reinventing Value Streams - Dennis, John (Productivity Press, 2025)
This book brilliantly illustrates how blockchain and Web3 are revolutionizing value exchange in society. Blockchain technology sets new standards for transparency, provenance, and traceability, benefiting every stakeholder across the value chain in an interoperable manner. The technology fundamentally transforms industries, verticals, and functions within organizations, enabling decentralized identity, asset tokenization, governance, and enhanced privacy. This book offers a deep yet accessible guide to navigating this new paradigm.-Alejandro Acua Rodrguez, Blockchain Infrastructure Specialist, CrossmintLean Thinking has its roots in ideas developed for process improvement in the 1900s. Systems Thinking was discussed as far back as the 1950s. Blockchain technology is based on work that started in the 1990s and was implemented soon after Satoshi Nakamoto published his Bitcoin whitepaper in 2009. Together, these three components-Lean, Blockchain, and Systems Thinking-provide a revolutionary force in process management efficiency and effectiveness.This book provides a perspective on the advantages of blockchain technology that is rarely covered in business books as well as specialist blockchain-related content. The focus has been the use of Cryptocurrencies as a store of financial value and as an instrument of speculation, like the stock market. This book shows that blockchain, together with Lean and Systems Thinking can provide multiple advantages for societies and the environment. It can be used effectively to meet sustainable development goals (SDGs).Readers will appreciate that blockchain within Lean practices and Systems Thinking opens opportunities for fundamental organizational transformation, improved strategic decision-making, increased interoperability, and a fairer, more sustainable, and less wasteful world. This book clarifies how the integration of blockchain technology as an organizational concept integrates Lean principles and Systems Thinking. This brings a transformative shift in process design, increasing productivity while minimizing waste across sectors such as industry, public services, governance, supply chains, and social frameworks.
Keywords: Blockchains (Databases); Industrial management.; elektronické knihy; electronic books